Industrial network security : securing critical infrastructure networks for Smart Grid, SCADA, and other industrial control systems - Knapp, Eric (Syngress, 2011)
For a decade now we have been hearing the same thing-that our critical infrastructure is vulnerable and it needs to be secured. Industrial Network Security examines the unique protocols and applications that are the foundation of industrial control systems and provides you with comprehensive guidelines for their protection. While covering compliance guidelines, attacks and vectors, and even evolving security tools, this book gives you a clear understanding of SCADA and Control System protocols and how they operate. Covers implementation guidelines for security measures of Critical Infrastructure Applies the security measures for system-specific compliance Discusses common pitfalls and mistakes and how to avoid them.